Development of on-site mixed mortar with hydrated lime for plastering - Leong, Jia Yin (2019)
Hydrated lime is a lime powder which contain mainly calcium hydroxide Ca(OH)₂ which produced from the limestone. As the calcium hydroxide will undergoes carbonation and will absorb carbon dioxide in the air, therefore, it may reduce the usage of cement if replacement of cement with hydrated lime is suitable to achieve particular purpose. Recently, there are many defects arising from cement-based mortar and lime-based mortar in construction industry, including the insufficient knowledge on producing an optimum ratio of cement-lime mortar has led to several issues in the industry, therefore, a research on cement-lime mortar has to be well-investigated. In the research and in order to fully utilize the hydrated lime, an optimum cement lime ratio has been determined and a deep understanding of its mechanical properties, durability performance and early-age behaviour on the replacement of cement with hydrated lime have to be studied. In current research, a series of engineering properties tests were carried out, including compressive strength test and density test. Water absorption test, capillary absorption test were carried out to study the properties of the mortar in term of durability. Results showed that the replacement of the cement with hydrated lime decreased the compressive strength of the examined specimens and also undermine the mechanical properties and durability properties of the structure. However, the mortar with hydrated lime provided a better surface and sense of touch when the optimum level of mortar was applied to the prototype. The mortar had greater adhesiveness and provided a smoother and aesthetic surface. Keywords: Hydrated Lime, Replacement, Engineering Properties, Durability Properties,Porosity